Design and Implementation of a Smart Automated Chess Board - thabet, Abdelrahman; Prasetyo, Judhi (Master Program in Mechanical Engineering, Gunadarma University, 2025)
This research presents the design and implementation of an innovative automated chessboard. The system autonomously moves chess pieces using a CoreXY motion system with an electromagnet end-effector, while real-time move detection is achieved through Hall Effect sensors. Powered by the Robot Operating System (ROS) on a Raspberry Pi running a competent chess engine, the board allows users to play against an intelligent opponent with varying difficulty levels. This project bridges the gap between traditional and digital chess, offering an innovative and interactive platform for entertainment and education.